Rehabilitation therapies for older clients of the Ontario home care system: Regional variation and client-level predictors of service provision - Armstrong, Joshua J.; Zhu, Mu; Hirdes, John P.; Stolee, Paul (Disability and Rehabilitation, 2015)
Purpose: To examine regional variation in service provision and identify the client characteristics associated with occupational therapy (OT) and physiotherapy (PT) services for older adults in the Ontario Home Care System. Methods: Secondary analyses of a provincial database containing comprehensive assessments (RAI-HC) linked with service utilization data from every older long-stay home care client in the system between 2005 and 2010 (n = 299 262). Hierarchical logistic regression models were used to model the dependent variables of OT and PT service use within 90 d of the initial assessment. Results: Regional differences accounted for 9% of the variation in PT service provision and 20% of OT service provision. After controlling for the differences across regions, the most powerful predictors of service provision were identified for both OT and PT. The most highly associated client characteristics related to PT service provision were hip fracture, impairments in activities of daily living/instrumental activities of daily living, cerebrovascular accidents, and cognitive impairment. For OT, hazards in the home environment was the most powerful predictor of future service provision. Conclusions: Where a client lived was an important determinant of service provision in Ontario, raising the possibility of inequities in access to rehabilitation services. Health care planners and policy makers should review current practices and make adjustments to meet the increasing and changing needs for rehabilitation therapies of the aging population.

Enquête sur l’offre active pour les services auxiliaires de santé du Nord-Est de l’Ontario - Bélanger, Roxanne; Mayer-Crittenden, Chantal; Mainguy, Josée; Coutu, Anie (Reflets, 2018)
Au Canada, il existe peu de données décrivant les services auxiliaires de santé en français disponibles dans les communautés francophones en situation minoritaire. L’objectif de cette étude était d’examiner l’accès aux services d’orthophonie, de physiothérapie et d’ergothérapie en français dans le Nord-Est de l’Ontario. Un outil mesurant la disponibilité et l’offre active des services a été créé et validé. Ce dernier a été distribué aux personnes fournissant les services et aux personnes les utilisant afin de déterminer leurs perceptions concernant l’offre de ces services en français, ainsi que l’accessibilité aux services auxiliaires de santé en français. Les résultats ont montré un manque de services en français dans cette région. Mots-clés : situation minoritaire francophone, services auxiliaires de santé, offre active, Nord-Est de l’Ontario, questionnaires